Rational Design of Li3V2(PO4)3/C for Phosphate-Based Symmetric Full-Cell Li-Ion Batteries - Ye-Wan Yoo; Hyeong-Seok Oh; Jong-Kyu Lee; Jung-Rag Yoon; Seung-Hwan Lee (Energy Material Advances)
To further increase the energy density of lithium-ion batteries (LIBs), various researches have been conducted on high-voltage and high-capacity cathode materials. In this perspective, monoclinic Li3V2(PO4)3 is a promising candidate due to its promising theoretical discharge capacity of 197 mAh/g with complex phase transition in the voltage range of 3.0 to 4.8 V. However, such asymmetric phase transition behavior with 3 Li+ ion extraction/insertion is highly irreversible, resulting in an initial discharge capacity of 163 mAh/g with deteriorated capacity retention. We suggest that cycling Li3V2(PO4)3 in the voltage range of 3.0 to 4.5 V suppresses the irreversible phase transition and elution of transition metal. Hence, Li3V2(PO4)3 in the voltage range of 3.0 to 4.5 V delivers an initial discharge capacity of about 142 mAh/g and exhibits extremely long cycle retention (78.70% 2,000 cycles), as when cycling in the voltage range of 3.0 to 4.3 V (81.67% 2,000 cycles). Furthermore, we present the possibility of a Li3V2(PO4)3||Li3V2(PO4)3 symmetric all-solid-state battery based on an N/P ratio and a cutoff voltage design, which is demonstrated in liquid electrolyte half-cells and symmetric full cells.